2005 IEEE 61st Vehicular Technology Conference
DOI: 10.1109/vetecs.2005.1543259
|View full text |Cite
|
Sign up to set email alerts
|

Time Variability of the Foliated Fixed Wireless Access Channel at 3.5 GHz

Abstract: Abstract-This paper examines the temporal characteristics of the fixed wireless access channel resulting from the combined effects of foliage and wind. Measurements at a frequency of 3.5 GHz taken over the course of one year are presented. The temporal variability of the path loss is shown to be well approximated by a Rician process. The dependency of the median K factor on excess path loss, average wind speed and season is investigated. An empirical expression for the median K factor encompassing these variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
2
13
1
Order By: Relevance
“…Moreover, they reported that the Rician K factor was found to vary exponentially with wind speed at frequencies of 0.9 GHz, 2 GHz, 12 GHz and 17 GHz in the controlled (anechoic chamber) and outdoor environments. However, different from their observations, the median Rician K factor in [52] is found to be approximately inversely proportional to averaged wind speed empirically based on the outdoor experimental data for a link up to 17 km over a period of 1 year at 3.5 GHz. Similar work for statistical Table 2.…”
Section: Wind Effectcontrasting
confidence: 89%
See 2 more Smart Citations
“…Moreover, they reported that the Rician K factor was found to vary exponentially with wind speed at frequencies of 0.9 GHz, 2 GHz, 12 GHz and 17 GHz in the controlled (anechoic chamber) and outdoor environments. However, different from their observations, the median Rician K factor in [52] is found to be approximately inversely proportional to averaged wind speed empirically based on the outdoor experimental data for a link up to 17 km over a period of 1 year at 3.5 GHz. Similar work for statistical Table 2.…”
Section: Wind Effectcontrasting
confidence: 89%
“…Recently, the relationship between the Rician K factor and averaged wind speed is found to be linear at 1.9 GHz as reported in [54]. From these works [46][47][48][49][50][51][52][53][54], it can be observed that the windinduced motion of the foliage medium can vary the tree shadowing effect temporally, and the temporal variation of the shadowing can be statistically modeled. Rician K factor is usually used to characterize the temporal shadowing effect.…”
Section: Model Expressionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been previously shown that the temporal characteristics of the fixed wireless channel follow a Rice distribution with the strongest impact being caused by wind and foliage [13,14]. The Rice distribution is characterized by a direct path, LOS component as well as multipath, scattered components existing in the received signal.…”
Section: Multipath Fading Modelmentioning
confidence: 99%
“…On the other hand, mainly suburban and rural areas are commonly surrounded by a large number of trees and hills. The presence of trees along the propagation path induces a significant signal fading on the radio wave propagation at frequencies above 1 GHz (Crosby, Abhayawardhana, Wassell, Brown, & Sellars 2005;Liou et al, 2009). Generally, trees appear as a single tree, line of trees or group of trees resulting in a different fading impact on the radio wave even at the same operating frequency (Ndzi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%